WOMEN EMPOWERMENT AND FAITH BASED REGULATION - Rosana, Yenni (LITERARY CRITICISM, 2015)
Women are human beings that should have rights as well as men. In the past women were only wives and mothers. However, nowadays many women achieve high positions in the workplace and social life. This achievement would be impossible without the work of feminist that have struggled to fight for women empowerment. This paper discusses women empowerment struggle and development process in comparison between Australia and Indonesia from the beginning to the contemporary era deals with faith of the communities. The reasons, of studying these two countries are because the two countries are different in levels of development and culture. Australia is developed country that recognizable as a very multicultural country where being engaged in a religion is not compulsory where Muslim people is minority among the population, the majority of Australian that belief in faith are Christian; meanwhile Indonesia is a developing country that has the biggest Muslim populations in the world. The methodology of writing will be study of published literatures on the issue. This paper will show how the two countries adapt ideological backgrounds of populations to support the women empowerment. Â Keywords : Women, Gender, faith, Muslim, Islam, Indonesia, Australia, Empowerment